PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Pada Pemerintah Kabupaten Indragiri Hulu) - Rio Safriadi; Muhammad Rasuli; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The present study aims to examine the budgetary participation and performance relationship in a public sector organization. It also attempts to examine whether perception of innovation mediate the budgetary participation and performance relationship. To collect data of this study, survey questionnaires are used. From 89 uestionnaires were given to managers in a public sector organization the district indragiri hulu, questionnaires with complete answers were 58 questionnaires (65.16%). A SPSS 17.0 with path analysis was utilized to examine the direct and indirect effects of budgetary participation on managerial performance with a significance level of 0,05 or 5%. The analysis results indicate that budgetary participation and managerial performance have positive relationship and statistically significant. Budgetary participation also directly affects perception of innovation. But budgetary participation did not indirectly affect managerial performance via the intervening variables of perception of innovation.   Keywords: budgetary participation, managerial performance, organization commitment, perception of innovation, public sectororganization